Semiquantitative assessment of fluorodeoxyglucose uptake in primary tumours on dynamic PET/computed tomography for lymph node metastasis evaluation in patients with lung cancer: a prospective study. Issue 11 (November 2020) - Yamanaka, Moriaki; Shinya, Takayoshi; Otomi, Yoichi; Kubo, Michiko; Arai, Yuta; Toba, Hiroaki; Bando, Yoshimi; Otsuka, Hideki; Harada, Masafumi
Abstract : Objective: To semiquantitatively estimate fluorine-18-fluorodeoxyglucose (FDG) uptake in primary lung cancer cells using dynamic and dual-time-point (DTP) PET/computed tomography (PET/CT) to obtain a diagnostic index for lymph node metastasis. Methods: Forty-five patients with lung cancer underwent dynamic and DTP PET/CT examinations. All primary lesions and lymph node metastases were evaluated pathologically. At each time phase, we assessed the maximum standardised uptake value (SUVmax), metabolic tumour volume (MTV) and total lesion glycolysis (TLG) of the primary tumours. We investigated the relationship between semiquantitative index and the presence of lymph node metastasis for each case and for all cases satisfying indications for segmentectomy. In cases with lymph node metastasis, we assessed the SUVmax of pathologically proven metastatic lymph nodes and nonmetastatic lymph nodes in each dynamic phase for evaluating temporal change. Results: Among 45 patients, 15 had 17 lymph node metastasis. SUVmax, MTV and TLG of primary tumours at each time phase were significantly associated with lymph node metastasis ( P < 0.05). In receiver operating characteristic analysis, dynamic second and third phases showed high diagnostic ability for lymph node metastasis. The temporal change in SUVmax in the dynamic phase between primary tumours and metastatic lymph nodes were significantly different ( P = 0.065). The temporal change in SUVmax was significantly lower in nonmetastatic lymph nodes than in primary tumours and metastatic lymph nodes ( P < 0.0001). Conclusions: Semiquantitative assessment of FDG uptake in dynamic second and third phases and the assessment of temporal changes in SUVmax on dynamic PET/CT scans were important predictors in diagnosing lymph node metastasis.